Phosphorylation of Endothelin-Converting Enzyme-1c at Serines 18 and 20 by CK2 Promotes Aggressiveness Traits in Colorectal Cancer Cells - Pérez-Moreno, Pablo; Quezada-Meza, Camila; Chavez-Almarza, Cristopher; Niechi, Ignacio; Silva-Pavez, Eduardo; Trigo-Hidalgo, César; Aguayo, Francisco; Jara, Lilian; Cáceres-Verschae, Albano; Varas-Godoy, Manuel; Díaz, Víctor M.; García de Herreros, Antonio; et al. (Frontiers in Oncology, 2020)
Endothelin-converting enzyme-1 (ECE1) activates the endothelin-1 peptide, which upregulates pathways that are related to diverse hallmarks of cancer. ECE1 is expressed as four isoforms differing in their N-terminal domains. Protein kinase CK2 phosphorylates the N-terminus of isoform ECE1c, enhancing its stability and promoting invasiveness of colorectal cancer cells. However, the specific residues in ECE1c that are phosphorylated by CK2 and how this phosphorylation promotes invasiveness was unknown. Here we demonstrate that Ser-18 and Ser-20 are the bona fide residues phosphorylated by CK2 in ECE1c. Thus, biphospho-mimetic ECE1cDD and biphospho-resistant ECE1cAA mutants were constructed and stably expressed in different colorectal cancer cells through lentiviral transduction. Biphospho-mimetic ECE1cDD displayed the highest stability in cells, even in the presence of the specific CK2 inhibitor silmitasertib. Concordantly, ECE1cDD-expressing cells showed enhanced hallmarks of cancer, such as proliferation, migration, invasiveness and self-renewal capacities. Conversely, cells expressing the less-stable biphospho-resistant ECE1cAA showed a reduction in these features, but also displayed an important sensitization to 5-fluorouracil, an antineoplastic agent traditionally used as therapy in colorectal cancer patients. Altogether, these findings suggest that phosphorylation of ECE1c at Ser-18 and Ser-20 by CK2 promotes aggressiveness in colorectal cancer cells. Therefore, phospho-ECE1c may constitute as a novel biomarker of poor prognosis and CK2 inhibition may be envisioned as a potential therapy for colorectal cancer patients.